Exploring the Resilience–Performance Relationship in Volleyball Players: a Pilot Study on Problem-Solving Strategies (Baltic Journal of Sport and Health Sciences, 2025)
Background: The purpose of this study was to investigate the relationship between resilience and the coping problems process in volleyball athletes. It is important for coaches and athletes to understand in depth the mechanisms underlying resilience, the effect of problem-solving strategies and the impact of these factors on the development of athletic performance. Methods: Participants included in the study were 52 volleyball players (male and female) across all national divisions in Greece, with the STARS (State – Trait Assessment of Resilience Scale, GR version) and the Problems Experienced Inventory (COPE, Greek version) used as evaluation instruments. A key requirement for participation in the study was that the participants must be over 14 years old and active athletes. The statistical analyzed with the statistical package SPSS IBM Statistics 27.0., using Pearson’s r, Cronbach’s’ α, and one-way ANOVA test with Bonferroni adjustments for independent samples.Results: No statistically significant differences were observed between the two genders of the participating athletes for resilience or for the coping problem strategies. Additionally, adding as a variable the training experience of participants, statistically significant differences were observed when the athletes had training experience of 8 years or more compared to athletes with less experience.Conclusion: It seems that years of training experience is a critical point for the formation of a mentally resilient profile as well as for the improvement of the ability to develop a strategic plan to address problems for volleyball players. Additionally, it seems that the factor that remained unaffected by the coaching process was the active problem-solving approach, which seems to be influenced by athletes’ personality already developed in the earlier years of their life. Future studies should investigate further these relationships between resilience and coping strategies using more participants and/or from other sport etc., or distinguish between individual and team sports.Key words: volleyball players, resilience, coping with problems, problem solving strategies